Experiences of Senior High School Mathematics Teachers With Higher Order Thinking Skills (HOTS) In Riau Islands Province-Indonesia - Ocy Dwi Rismi; Wardani Rahayu; Makmuri Makmuri (Jurnal Gantang, 2021)
Higher-order Thinking Skills (HOTS) are essential for students, and teachers must properly train and handle them. This study aims to explain mathematic teachers' learning preparation and experiences, evaluate mathematic teachers' perception of HOTS, investigate mathematic teachers' efforts to improve HOTS for senior high school students in Riau Islands Province, Indonesia, and to find out students’ HOTS ability. One hundred and twelve senior high school mathematic teachers in the Province of Riau Islands were the sample of this survey. Experts validated the research instrument, which is in the form of an updated questionnaire. A descriptive statistic was used to evaluate the results (in percentage). The findings revealed that students' HOTS potential in Riau Islands Province is still lacking. The Riau Islands Province senior high school mathematic teachers did a good job of planning the class, but it was not done consistently. Some teachers did not completely plan the lessons according to the educational standards that were recommended. Teachers' most difficult challenge in raising student HOTS during the mathematics learning process was deciding on an engaging stimulus that was suitable for the nature of the material to be taught. The teachers' understanding of HOTS is sufficiently broad, and they believe that HOTS should be taught to students.